Associations between Maternal AFP and β-HCG and Preterm Birth - Wang, Xu; Chen, Ying; Kuang, Hualong; Yang, Rui; Chen, Daozhen; Chen, Ailing; Feng, Yaling; Dai, Jianrong; Wang, Ting; Wang, Yun (American Journal of Perinatology, 2019)
Objective Preterm birth (PTB) is a significant public health problem. We aimed to explore whether alpha fetal protein (AFP) or β-human gonadotropin (β-HCG) levels during pregnancy were associated with PTB in Chinese population.Study Design The clinical data collected Nanjing Medical University Affiliated Suzhou Hospital and Wuxi Maternity and Child Health Care Hospital between January 2006 and December 2011 were analyzed retrospectively. A total of 64,999 pregnant women were registered. In addition, 13,828 pregnant women were collected serum from the second trimester. The maternal serum AFP and β-HCG were measured by enzyme immunoassay.Results In our study, the rate of PTB is 6.23%. With each unit increase of maternal AFP concentration, the adjusted odds of PTB was increased by 69.3% (odds ratio = 1.693, 95% confidence interval: 1.434–1.999, p = 0.00). We set AFP concentrations as high, medium, and low levels. When comparing with low concentration of AFP, high concentration of AFP (≥1.179 M) was positively associated with PTB with adjustment for potential confounders (p < 0.05). Nevertheless, no statistically significant associations were observed between maternal β-HCG and PTB.Conclusion In this study, maternal AFP concentration was associated with increased risk of PTB.
Keywords: AFP; β-HCG; preterm birth; China